EXECUÇÃO PROVISÓRIA DA PENA NO PROCEDIMENTO DO TRIBUNAL DO JÚRI EM FACE DO PRINCÍPIO DA PRESUNÇÃO DE INOCÊNCIA - FANUEL SOUZA DOS SANTOS (2023)
SANTOS, Fanuel Souza dos. Provisional execution of sentence in the Jury´s Court procedure in face of the principle of presumption of innocence. Advisor: Rejane Alves de Arruda. 2023. 100 f. Dissertation (Master in Law) – Faculdade de Direito, Universidade Federal de Mato Grosso do Sul, Campo Grande, 2023. This research analyzes the unconstitutionality or constitutionality of the alteration made by Law no. 13,964, of December 24, 2019 – Anti-Crime Package – of article no. 492, item I, item “e” of the Code of Criminal Procedure (Decree-Law No. 3689, of October 3, 1941) and has the general objective of promoting the strengthening of Freedoms, Rights and Individual Guarantees. The specific objective is to investigate, within the scope of the Jury Court, the early application of the penalty in sentences equal to or greater than 15 years within a constitutional perspective of Fundamental Rights and Guarantees and Criminal Procedure. The hypothetical-deductive method and diagnostic approach, of the documental analysis and systematic literature review type, uses documental data that present quantitative numbers of sentences handed down by the Jury Court of the State of Mato Grosso do Sul with merit and without merit and the resulting analysis of the amendment of article no. 492, item I, item “e” of Law no. 13,964/2019. The results of the comparative analysis of the data provided allowed us to perceive that the number of judgments handed down in the years 2019, 2020 and 2021 (on trial with and without merit) total 3,816 and the number of judgments in the event of a judgment in the same period amounts to a quantum of 473. Of the sentences with sentences of 15 years or more, there were 1,134, in the years 2019 to 2021 with 540, 276 and 318 respectively. Of the sentences aged 15 years or more that were appealed, the total number of judgments is 543, of which: 03 annulled judgments, 01 decision reform, 275 confirmed sentences, 20 reformed-acquittal sentences and 244 reformed-conviction sentences. The results show the important consideration of the presumption of innocence and the principle of non-culpability, justifying the research in the face of the 20 cases that in the end obtained acquittal in sentences with 15 years or more. Likewise, it seeks to analyze the constitutional principles of human dignity, sovereignty of verdicts and fullness of defense. The study carried out is of a bibliographical and documental nature, based on legislation, doctrines (printed or online), scientific journals, books, dissertations, monographs, theses, scientific articles, international and domestic documents, among others, on the subject at hand. Keywords: Jury Court; provisional execution of penalty; presumption of innocence.